2009
DOI: 10.1007/s12033-009-9232-2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, Purification, and Characterization of a Novel Esterase from Lactobacillus plantarum

Abstract: Lactobacillus plantarum is an important lactic acid bacterium, usually found as natural inhabitant of food, such as fermented vegetables and meat products. However, little information about lactic acid bacteria, especially concerning L. plantarum, as a source of useful enzymes has been reported. The aim of this study was to clone, express in Escherichia coli, purify, and characterize an esterase from L. plantarum ATCC 8014. The esterase gene (1014 bp) was amplified and cloned in pET14b expression vector to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Numerous reports have been published on the cloning and expression of microbial esterases (Brod et al 2010;Huang et al 2010;Terahara et al 2010;Ro et al 2004;Khalameyzer et al 1999). When considering heterologous expression, one needs to investigate the type of expression system to be applied, as this could have a significant effect on the level of enzymes produced.…”
Section: Heterologous Production Of Esterasesmentioning
confidence: 99%
“…Numerous reports have been published on the cloning and expression of microbial esterases (Brod et al 2010;Huang et al 2010;Terahara et al 2010;Ro et al 2004;Khalameyzer et al 1999). When considering heterologous expression, one needs to investigate the type of expression system to be applied, as this could have a significant effect on the level of enzymes produced.…”
Section: Heterologous Production Of Esterasesmentioning
confidence: 99%
“…Esterases that originate from wine LAB are responsible for both the biosynthesis and hydrolysis of esters (Matthews et al, 2004;Sumby et al, 2009;Brod et al, 2010). Oenococcus oeni, as well as species of Lactobacillus and Pediococcus, is able to hydrolyse esters and Matthews et al (2006) found that significant esterase activity levels remained under wine-like conditions.…”
Section: Malolactic Fermentation Must and Wine Composition Before Inomentioning
confidence: 99%
“…There is great variation between species and genera with regards to their esterase activity and from available literature, it seems as if O. oeni displays the greatest activity, compared to lactobacilli and pediococci (Matthews et al, 2006). Recently, Brod et al (2010) characterised a novel esterase from L. plantarum and found substrate specificity towards p-nitrophenyl-linked substrates, similar to that of O. oeni (Matthews et al, 2006).…”
Section: Malolactic Fermentation Must and Wine Composition Before Inomentioning
confidence: 99%
See 1 more Smart Citation
“…Lactobacillus plantarum is a lactic acid bacterial species that is most abundant in fermenting plant-derived raw materials and also might colonize the human gastrointestinal tract considerably better than other tested lactobacilli (10). Although several esterase enzymes have been described in L. plantarum (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), cinnamoyl esterase activity has not been found yet.Feruloyl esterases constitute an interesting group of enzymes with a potentially broad range of applications in the food industry, and there is a constant search for such enzymes with more desirable properties for novel food applications; the present study represents the description of a feruloyl esterase enzyme in L. plantarum that is widely distributed among strains of the species. …”
mentioning
confidence: 99%